Critical nitrogen and potassium levels and sufficiency ranges for banana cultivation in Ecuador - Villasenor-Ortiz, D. [UNESP]; Prado, R. De Mello [UNESP]; Luna-Romero, E.; Jaramillo-Aguilar, E.; Agurto-Rodriguez, L. (Int Soc Horticultural Science-ishs, 2022)
Introduction - Banana cultivation plays a fundamental role in Ecuadorian economy. For this reason, aspects such as plant nutrition, particularly nitrogen and potassium, which guarantee high production, are vital for the sustainability of agribusiness in this country. Materials and methods - We evaluated the effects of nitrogen and potassium (K40) fertilization on the nutritional status and production of the Williams Cavendish' banana cultivated in Ecuador. The treatments consisted of a 4 x 4 factorial scheme with four doses of N (0, 200, 400, and 600 kg ha(-1)) combined with four doses of K2O ( 375, 750, and 1,125 kg ha(-1)) arranged in a randomized design with four replications. We performed chemical analyses of the soil and plant leaves and determined the concentrations of different nutrients, after which we compared the results among different treatments. Results - We observed a combined effect of these nutrients (N and K20) on the leaf contents of K, Ca, Mg, S, CI, Mn, and Zn. Nitrogen and potassium fertilization improved the nutritional status of banana plants, reaching the appropriate range of N equal to 32-33 g kg-' and K equal to 34-35 g kg(-1) for bananas cultivated in Ecuador. The maximum production of banana depended on the interaction between N and K, and it was associated with the doses of N and K20 equal to 358 and 596 kg ha(-1), respectively.
Keywords: leaf analysis; Musa spp.; nutritional diagnostic indexes; plant nutrition